The metabolic syndrome in normal weight Malay subjects (Bangladesh Journal of Medical Science, 2016)
Information regarding the prevalence of features of Metabolic Syndrome (MS) in Malaysia has not been previously reported. There are also difficulties in using Western cut-off criteria to define MS in this Asian population. The aim of this study was to determine the prevalence of features of MS in normal body weight normoglycemic Malay subjects. An additional aim was to determine the optimal waist circumference cut-off which best identified MS in this population. We used data from a cross-sectional study carried out in Malay descendants in Kota Bharu a city on east coast peninsular Malaysia. The prevalence of different features of MS was determined using the AHA/NHLBI and IDF criteria. The results showed that even after excluding subjects with diabetes mellitus, impaired glucose tolerance (IGT) or impaired fasting glucose (IFG), hypertension, a first degree relative with diabetes mellitus and obesity (BMI >25 kg/m2), the features of metabolic syndrome were still highly prevalent in this population. Furthermore, the features of the metabolic syndrome were associated with reduced insulin sensitivity in an additive manner. The metabolic syndrome is a biologically relevant construct for the identification of the insulin resistant individual in a Malaysian population.Bangladesh Journal of Medical Science Vol.15(1) 2016 p.123-128